Biophysical disturbances of elephant safaris in the Royal Chitwan National Park, Nepal - Subedi, Bodh Raj (Banko Janakari, 2017)
The paper explores peoples' perceptions on the biophysical impacts of elephant safaris which is a perfect way to go wildlife viewing, and is very eco-friendly. It surpasses its alternatives, especially noisy Jeep safaris. However, more people are becoming aware of the biophysical impacts of the safaris in the park. They perceived that the safaris cause negative impacts on wildlife and can destroy habitat through soil compaction and erosion, vegetation damage and disturbances. The study also estimated that the current wildlife observation distance from elephant safaris are less than fifteen metres which is too close and may be harmful to wildlife. This study provides interesting comparisons with previous studies on impacts of tourist activities on wildlife from a biological perspective in that the appropriate distances perceived by park staff to view wildlife was the only one to “fit" their findings. The distances perceived by other groups of people as appropriate would in fact, cause unacceptable levels of disturbance. It is concluded that social (human) perception of disturbance by elephant safaris may not accurately reflect the biological severity of their impacts.